Frequency and characteristics of circulating CD4+ CD28null T cells in patients with psoriasis. (8th October 2015) - Lima, X.T.; Cintra, M.L.; Piaza, A.C.; Mamoni, R.L.; Oliveira, R.T.; Magalhães, R.F.; Blotta, M.H.
Summary: Background: Psoriasis is a chronic inflammatory disease that affects the skin. CD4 + CD28 null cells are a subset of T lymphocytes associated with systemic inflammation and increased cardiovascular disease risk, and may be involved in the pathogenesis of psoriasis. Objectives: To study the features of circulating CD4 + CD28 null cells in patients with psoriasis, adjusted for the influence of known cardiovascular disease risk factors. Methods: Forty‐two patients with psoriasis and 42 controls entered the study. Peripheral blood mononuclear cells were analysed for the frequency of CD4 + CD28 null T lymphocytes and their expression of cytotoxic granules and homing receptors. Immunostaining for cutaneous cytotoxic granules was assessed in skin biopsies from 11 patients. Results: There were no differences in the frequency of CD4 + CD28 null T cells between groups in all situations analysed. However, there was an increased number of cells expressing cytotoxic granules and a decreased number expressing CXCR3 in ex vivo samples of patients with psoriasis. A negative correlation was observed between the frequency of ex vivo CD4 + CD28 null cells and psoriasis severity. After clinical remission in nine patients, ex vivo CD4 + CD28 null lymphocytes expressing cytotoxic granules decreased. Perforin‐, granzyme B‐ and granulysin‐containing cells were found in skin lesions. Patients with psoriasis also had increased plasma levels of C‐reactive protein. Conclusions: These data suggest that cytotoxic cells, such as CD4 + CD28 null lymphocytes, within an inflammatory environment may play a role in the pathogenesis of psoriasis. Abstract : What's already known about this topic? CD4 + CD28 null T lymphocytes expand as a result of systemic inflammation and are involved in the pathogenesis of chronic inflammatory diseases, such as rheumatoid arthritis, ulcerative colitis and psoriatic arthritis. What does this study add? Our study suggests that CD4 + CD28 null lymphocytes may play a role in the pathogenesis of psoriasis. This is evidenced by an increased number of circulating cells expressing cytotoxic granules in patients with psoriasis and the presence of granule‐containing cells in skin lesions. Linked Comment: Eaton et al. Br J Dermatol 2015; 173: 891–892 .